2007
DOI: 10.1111/j.1365-313x.2007.03051.x
|View full text |Cite
|
Sign up to set email alerts
|

Early chloroplastic alterations analysed by optical coherence tomography during a harpin‐induced hypersensitive response

Abstract: SummaryThe hypersensitive response has been mostly studied by molecular and biochemical methods after sample destruction. The development of imaging techniques allows the monitoring of physiological changes before any signs of cell death. Here, we follow the early steps of a hypersensitive-like response induced by the bacterial elicitor harpin in Nicotiana sp. We describe cytological modifications after inoculation of the harpin protein, using confocal fluorescence microscopy (CFM) and optical coherence tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…It has been shown that Ca 2 + regulates FBPase 42,43 , and the stability of the photosystem II and thylakoid O 2 evolving complexes 44 . Th e stromal Ca 2 + transients coincide with the stress-induced rapid downregulation of photosynthesis 39,45,46 . Importantly, photosynthesis collapse may lead to photo-induced production of ROS including 1 O 2 (ref.…”
Section: Days After Inoculation ( D ) Ion Leakage At 3 Days After Inmentioning
confidence: 90%
“…It has been shown that Ca 2 + regulates FBPase 42,43 , and the stability of the photosystem II and thylakoid O 2 evolving complexes 44 . Th e stromal Ca 2 + transients coincide with the stress-induced rapid downregulation of photosynthesis 39,45,46 . Importantly, photosynthesis collapse may lead to photo-induced production of ROS including 1 O 2 (ref.…”
Section: Days After Inoculation ( D ) Ion Leakage At 3 Days After Inmentioning
confidence: 90%
“…This is suggested by the harpin-induced modifications in the reflective index of the membranes observed by optical coherence tomography (53). Stress-induced changes in the organization of thylakoid structure and composition can decrease PSII and photosystem I activities (54).…”
Section: Harpin Elicitation Inactivates Psii and Induces Ros Accumulamentioning
confidence: 99%
“…Cellular-level resolution images of various ophthalmic tissues [51], embryos and plants [24,25,52,53] have been published. A few other examples obtained with the FF-OCM technique described in this chapter are presented in this section.…”
Section: Illustration Of Imaging Capabilitiesmentioning
confidence: 99%